EVALUATION THROUGHT THE USE OF A CHECK LIST OF THE ORGANIZATION AND ERGONOMIC CONDITION OF THE WORK STATIONS CHAIR, TABLE, KEYBOARD, COMPUTER TERMINAL LEVEL OF LOCALIZED PAIN LUMBAR RISCK OF THE ADMINISTRATIVE EMPLOYES OF UNIEVANGELICA. (Fiep Bulletin - online, 2015)
Since the 18 and 19 centuries there has been a consolidation of the industrial society and substantial changes were introduced to the work atmosphere: tools, machines and equipment work hours and the type and form of work organization.These changes impacted the lives and health of people, especially those of the employees, Bisso (1990). The objective of this study was to evaluate, through the use of a check list, the organization and the ergometric, condition of the work stations of the administrative employees of UniEvangélica. Thirty employees of UniEvangélica between the ages of 20 and 50, men and women. From the administrative sector (sectors with computers ) volunteered to participate in the study. The treatment of statistics used frequency analysis. The results indicated the ergometric condition in general of the work stations are as follows: 16,7% good, 16,7% reasonable, 63,3% poor and 3,3% unacceptable, biomechanical conditions of the work stations are as follows: 16,7% good, 16,7% reasonable, 63,3% poor and 3,3% unacceptable. Simplified evaluation of lumbar risk: 10,0% very little risk, 13,3% little risk, 6,7% moderate risk. Evaluation of chair, table and keyboard: 3,3% excellent, 10,0 % good, 3,3% reasonable, 73,3% poor and 10,0% unacceptable. Evaluation of the work stations: 3,3% excellent, 13,3% good, 6,6% reasonable, 66,7% poor and 10,0% unacceptable. We conclude, that as a randon sample, ergometric conditions of the work stations of the administrative employees of UniEvangélica are in poor condition, suggest that an evaluation be made of all administrative work stations.
Keywords: check list; work station; ergometric condition; lumbar risk.